EFEKTIVITAS PENYALURAN DANA ZIS BIDANG PENDIDIKAN DI MASA PANDEMI COVID-19 PADA BAZNAS KOTA TANGERANG SELATAN - Nurfitri Arsita, (2022)
The covid-19 pandemic has had an impact on all sectors, one of which is the education sector, causing the dropout rate to increase. Zakat instruments also help to accelerate recovery from the impact of covid-19. The distribution of ZIS funds in the education sector by ZIS management institutions will have an effect if they are used effectively, on target, and optimally. The purpose of this study was to determine the effectiveness of the distribution of ZIS funds in the education sector during the covid-19 pandemic at the South Tangerang City Baznas. The method used in this research is descriptive qualitative analysis through case studies. The data used are qualitative data sourced from primary data through interviews, observations, and secondary data collected through library research, documentation. The validation technique used is triangulation, and the researcher reduces the data and draws conclusions. The results showed that the distribution of ZIS funds in the education sector during the covid-19 pandemic at the South Tangerang City Baznas had run effectively using four indicators in measuring effectiveness, namely targeting accuracy, program socialization, achievement of program objectives, and program monitoring.